Research on evaluating laser welding quality based on two-dimensional array ultrasonic probe. Issue 5 (May 2016) - Zhou, Guanghao; Xu, Guocheng; Gu, Xiaopeng; Liu, Jing
Abstract In this paper, an evaluating method of laser welding quality for stainless steel lap joint has been studied based on the ultrasonic nondestructive testing technology. The two-dimensional array ultrasonic probe is used to inspect the weld joint, analyzing the effect of fusion state on A-scan echo amplitude, and C-scan image of internal contact surface is established. A concept of equivalent weld width as the quantitative characterization of fusion state is defined, and a computational model of equivalent weld width is discussed based on statistical method. Testing results show that this method is simple and feasible, and its accuracy could completely meet the requirements of engineering application.